Creating of Semi Automatic Cassava Cutting Machine for Enhancing Creative Economy of Karihkil Village Community - Dwita Suastiyanti; Gerrit Risaldi; Wahyudi Wijaya; Bambang Agus Topan (Institute for Research and Community Services, 2020)
The rapid progress of the modern age, especially the development of technology towards industry 4.0, requires people to work more effectively and efficiently by trying to replace the traditional work patterns that rely heavily on human labor with machines,. In the village of Karihkil, Ciseeng, Bogor Regency, there are many home-industry manufacturers of various cassava chips. This business is still done manually so that it affects the quality and quantity of cassava chips they produce. This business opportunity needs to be developed further by increasing the cutting capacity of the cassava chips, given the fact that the manufacturers still use manual cassava cutting tools. In this present community-service activity the cassava chopper machine was designed and fabricated with a motor drive source (using a crank rotation) so that an increase in production results would be obtained by accelerating the process of cutting cassava into chips. This chopping machine was designed to work simultaneouly with the frying process so that the whole process occurred only once to obtain cassava chips ready for packaging. By using this new process, there was an increase in the production of cassava chips by two times. In addition, the thickness (1 mm) and dimension (diameter 3 cm) of cassava chips were consistently produced. This machine was also designed to overcome existing deficiencies with manual workmanship such as irregular cutting thickness and cracked cuts.